The Referrer Matters. Musculoskeletal Surgical Conversion Rates: A Systematic Review With Meta-Analysis - Darryn Marks; Jasmine Pearce-Higgins; Taylor Frost; Joseph Fittock; Evelyne Rathbone; Wayne Hing (Health Services Insights)
Background: Efficient musculoskeletal care is important for health services and society. Surgical conversion rates are a common measure of efficiency, yet normal values and the impact of referrer type are unclear. This information could assist musculoskeletal care, service benchmarking and redesign. Methods: A systematic review with meta-analysis was undertaken with PubMed, CINAHL and EMBASE databases searched from inception to 12th of October 2024, to identify studies from which musculoskeletal surgical conversion rates could be extracted. Data were categorised according to the professional group responsible for referral (all doctors, general practitioners, sports physicians, allied-health/physiotherapy-led screening services) and methodology used to define surgical conversion. Meta-analysis of pooled data was undertaken. Results: Twenty-eight studies with a combined total of 5358 patients were included. Pooled data revealed surgical conversion rates of 23% for referrals from all types of doctors (0.23, 95% CI 0.18-0.27), 28% from general practitioners (0.28, 95% CI 0.12-0.52), 61% from allied health physiotherapy-led screening services (0.61, CI 0.50-0.70) and 70% from sports physicians at (0.70, CI 0.64-0.75). A variety of methodological factors impacted surgical conversion rate reporting and heterogeneity. Conclusions: Musculoskeletal services seeking to improve efficiency through higher surgical conversion rates, should include sports physician and/or physiotherapy-led models of care for referral generation or management.